Engineering and Humanities Students' Strategies for Vocabulary Acquisition: An Iranian Experience - Soodmand Afshar, Hassan; Moazam, Ismail; Radi Arbabi, Hassan (Linguistik Online, 2014)
The present study set out to investigate the differences between EAP (English for Academic Purposes) students of Humanities and Engineering in terms of vocabulary strategy choice and use. One hundred and five undergraduate Iranian students (39 students from Engineering Faculty and 66 from Humanities Faculty) studying at Bu-Ali Sina University Hamedan, during the academic year of 2011–2012 participated in this study. For data collection purposes, a pilot-tested factor-analyzed five-point Likert-scale vocabulary learning strategies questionnaire (VLSQ) containing 45 statements was adopted. The results of independent samples t-test indicated that, overall, the two groups were not significantly different in the choice and use of vocabulary learning strategies. However, running Chi square analyses, significant differences were found in individual strategy use in 6 out of 45 strategies. That is, while Humanities students used more superficial and straightforward strategies like repetition strategy and seeking help from others, the Engineering students preferred much deeper, thought-provoking and sophisticated strategies like using a monolingual dictionary and learning vocabulary through collocations and coordinates. Further, the most and the least frequently used vocabulary learning strategies by the two groups were specified, out of which only two strategies in each category were commonly shared by both groups. The possible reasons why the results have turned out to be so as well as the implications of the study are discussed in details in the paper.